Influence of step faceting on the enantiospecific decomposition of aspartic acid on chiral Cu surfaces vicinal to Cu111. Issue 75 (26th August 2016) - Reinicker, A. D.; Therrien, A. J.; Lawton, T. J.; Ali, R.; Sykes, E. C. H.; Gellman, A. J.
Abstract : The crystallographic orientation of chiral step facets created byl -aspartic acid adsorption dictates enantioselectivity on chiral surfaces vicinal to Cu111. Abstract : On surfaces vicinal to Cu111, l -aspartic acid (l -Asp) adsorption causes steps to facet enantiospecifically into 310 R and 320 S steps.l -Asp has its highest heat of adsortion on surfaces that naturally expose the 310 R or 320 S steps but decomposes preferentially on the 310 R steps.